THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF FORMING DEONTOLOGICAL COMPETENCE IN MEDICAL STUDENTS (SCIENCE TIME JOURNAL, 2026)
The modernization of healthcare systems and the rapid development of medical science require highly qualified physicians possessing not only professional knowledge and clinical skills but also strong moral values and ethical responsibility. Under these conditions, deontological competence has become an essential component of professional training in medical education. The purpose of this study is to analyze the theoretical and methodological foundations of developing deontological competence among medical students and to determine its structural components, functions, criteria, and pedagogical conditions for effective formation. The study is based on competence-based, axiological, systemic, and personality-oriented approaches. The results indicate that deontological competence represents an integrative professional quality combining ethical knowledge, value orientations, communication skills, professional responsibility, empathy, and reflective abilities. The article substantiates the necessity of integrating deontological training into all stages of medical education and highlights the role of innovative pedagogical technologies in preparing professionally competent and socially responsible physicians.